The client kings of Emesa: a study of local identities in the Roman East - Konrad, Michaela (Syria, 2017)
The dynasts of Emesa, today Homs in northwest Syria, ranked among the most important of the Roman allies at the eastern fringe of the Roman Empire. For good reasons the Roman cemetery of Tall Abū Ṣābūn has been identified as necropolis of the royal family. The finds from the 22 tombs of the early and mid of the 1st cent. ad uncovered under the direction of H. Seyrig in 1936 and a tomb monument with pyramidal roof that has been blown up in 1911 have provided valuable information about the cultural history and identity of the client kingdoms in the 1st cent. bc and ad. The objects, mainly clothing accessories, jewellery, weapons and parts of the tomb furniture have recently been subject of a detailed analysis. It reveals a changing self-image of the oriental client kings going together with intensified contacts with Rome. But whereas the burial customs show clear local traditions until the mid of the 1st century the jewellery and insignia show striking parallels to the cultures of the Central-Asian steppe. In the case of Emesa these characteristic items, that originally unified the local elites of the steppe-desert, seem to disappear with the liquidation of the client status in the early 70ies ad, and were substituted by Roman forms of representation. In consideration of the written sources this case study discusses the parameters of identity and identitary change of the eastern client kings in their interaction with Rome. The results reveal that care for control and safety on the eastern fringe of the Roman Empire was only one aspect of their specific role. However their full significance becomes only understandable by regarding the complex cultural, social, political and economic situation in Syria in the 1st cent. ad.